2017
DOI: 10.1002/jmv.24829
|View full text |Cite
|
Sign up to set email alerts
|

Serum and exosomal miR‐122 and miR‐199a as a biomarker to predict therapeutic efficacy of hepatitis C patients

Abstract: MicroRNA (miRNA), which has been shown to correlate with liver functions, has been proposed as a new biomarker reflecting liver injury. The aim of the study was to investigate miRNA-122 (miR-122) and mir-RNA-199a (miR-199a) as a biomarker for predicting therapeutic efficacy in hepatitis C (HepC) patients. A total of 47 HepC 1b patients and 16 healthy subjects were enrolled in the study. Serum and exosomal mir-RNAs and other conventional biomarkers reflecting liver function were evaluated. The miR-122 levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 31 publications
(67 reference statements)
1
25
0
Order By: Relevance
“…However, serum exosome-derived miRNAs are different from the total serum miRNAs. A previous study determined that there were no correlations between serum miR-126 and exosomal miR-126 (28), and another study demonstrated that serum miR-122 and miR-199a were potential biomarkers that reflect antiviral therapy efficacy in patients with hepatitis C (29); however, to the best of our knowledge, there is no evidence that exosomal miR-122 and miR-199a have the same predictive effect.…”
Section: Characteristicmentioning
confidence: 82%
“…However, serum exosome-derived miRNAs are different from the total serum miRNAs. A previous study determined that there were no correlations between serum miR-126 and exosomal miR-126 (28), and another study demonstrated that serum miR-122 and miR-199a were potential biomarkers that reflect antiviral therapy efficacy in patients with hepatitis C (29); however, to the best of our knowledge, there is no evidence that exosomal miR-122 and miR-199a have the same predictive effect.…”
Section: Characteristicmentioning
confidence: 82%
“…8287 For example, serum exosomal miR-122, miR-134, miR-424-3p, miR629-5p, and miR-199a are candidate biomarkers for HCV. 8284 and serum exosomal miR-214 is a potential biomarker for liver fibrosis. 85 Human biliary EVs contain abundant miR species, of which miR-191, miR-486-3p, and miR-1274b can be used to diagnose cholangiocarcinoma (CCA).…”
Section: Evs As Potential Biomarkers For Liver Diseasesmentioning
confidence: 99%
“…4a). Previous studies have shown that during HBV infection, circulating miR-122 levels correlate with liver damage [21] while liver miR-122 levels significantly decrease exhibiting a reverse relationship with inflammation and viral load [21]. Lower HBV DNA levels in both HBsAg carriers and acute HBV patients infected with HEV suggests lowering of HBV replication.…”
Section: Discussionmentioning
confidence: 97%
“…These miRNAs exhibit a consistent expression profile among healthy individuals. miR-122, the most abundant hepatic microRNA, has been evaluated mainly in chronic hepatitis B virus (HBV), hepatitis C virus (HCV) infections and hepatocellular carcinoma (HCC) [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%